Evaluation of arm stroke technique in front crawl swimming - Suito, H.; Shinkai, H.; Nunome, H.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of the present study was to evaluate the high elbow technique in arm stroke motion, and to investigate the relationship between the technique and the swimming performance in front crawl swimming. Subjects were fourteen skilled male swimmers and five unskilled male swimmers. The arm stroke motions of subjects were captured threedimensionally (3-D) at 60 Hz during 25 m front crawl swimming. A new index of the high elbow arm stroke technique (high elbow index) was developed. The index was defined by the 3-D coordinates of the three joints (shoulder, elbow and wrist). As the result, the arm stroke technique of the skilled swimmers was different compared with the unskilled swimmers. Moreover, a significant correlation was obtained between the index and the swimming velocity. The results indicated that the index was effective to evaluate the arm stroke technique and the high elbow technique was effective for improvement of the swimming performance in front crawl swimming.